STUDI KELAYAKAN PEMBUKAAN PRODI MAGISTER PENDIDIKAN BAHASA DAN SASTRA INDONESIA - Syafruddin, Syafruddin; Ananda, Refisa; Supratmi, Nunung; Hartati, Rahma Dewi; Badriyah, Ratu; Pratiwi, Brillianing; Suparti, Suparti (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
The opening of a new study program at an institution must meet several aspects, including feasibility studies. The feasibility study can provide an overview of the prospects of the Study Program that will be opened. FKIP Universitas Terbuka (UT) has several potentials that can be considered to open a new Master of Education study program Indonesian. This research aims to produce an academic paper in the form of recommendations to UT leaders about whether or not the plan to open the Master of Education Study Program Indonesian be opened based on a) The response of prospective Master students to the plan to open a PJJ-based Indonesian Education Study Program; b) The competence of Master of Education graduates Indonesian needed by the community; c) Response from education experts (Association/reviwer Ban PT) to the feasibility of organizing a PJJ-based Indonesian Education S2 study program. The research method uses a descriptive design by conducting a survey in the form of questionnaire distribution, based on region. The results of the questionnaire data collection were analyzed using quantitative methods, then the FGD (interview) data was analyzed qualitatively using SWOT analysis. The research population of (1) undergraduate students of UT Indonesian Education who have programmed the TAP (Final Project Program) course, (2) Participants. Sampling using Proportional Area Random Sampling technique. The results showed that UT has the potential to open a Master of Education Indonesian study program. However, it is still necessary to develop and discuss in detail the curriculum that will be offered to prospective students.